2011
DOI: 10.1097/ajp.0b013e31821c29d3
|View full text |Cite
|
Sign up to set email alerts
|

Increased Pain Sensitivity Is Not Associated With Electrodiagnostic Findings in Women With Carpal Tunnel Syndrome

Abstract: The similar widespread pressure and thermal hypersensitivity in patients with minimal, moderate, or severe CTS and pain intensity suggests that increased pain sensitivity is not related to electrodiagnostic findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 36 publications
4
42
0
1
Order By: Relevance
“…This means that the symptoms of CTS are correlated more with psychological status of the patient rather than the electrophysiological severity of the disease. The subjective-objective discordance in CTS severity observed here and in few other studies[13] goes in hand with observations stating that illness behavior is a better predictor of pain intensity in CTS and musculoskeletal pain syndromes than demographic factors and objective measures of disease activity. [1516] This is practically important as well since the release of entrapment alone may not alleviate the symptoms of CTS.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…This means that the symptoms of CTS are correlated more with psychological status of the patient rather than the electrophysiological severity of the disease. The subjective-objective discordance in CTS severity observed here and in few other studies[13] goes in hand with observations stating that illness behavior is a better predictor of pain intensity in CTS and musculoskeletal pain syndromes than demographic factors and objective measures of disease activity. [1516] This is practically important as well since the release of entrapment alone may not alleviate the symptoms of CTS.…”
Section: Discussionsupporting
confidence: 58%
“…[12] Although electrophysiology is very important in confirming the diagnosis, electrodiagnostic stratification may not be corroborating with pain sensitivity. [13] Why some patients with milder entrapment have severe symptoms? Does psychological factors have any role in increasing pain sensitivity and hence severity of symptoms?…”
Section: Discussionmentioning
confidence: 99%
“…46 Nevertheless, in an earlier study, we found that widespread pressure pain hypersensitivity was not a prognostic factor for physical therapy treatment. 12 Therefore, it is possible that the degree of central sensitization seen in CTS plays an important role in changes in pressure pain sensitivity after the application of any therapeutic intervention.…”
Section: Limitationsmentioning
confidence: 94%
“…18,51 In fact, the magnitude of widespread pressure hypersensitivity is not significantly different between minimal, moderate, or severe CTS, suggesting that this may be a common feature in this condition. 12 Further, it has been demonstrated that subjects with signs and symptoms of CTS exhibit increased sensitivity (temporal summation), suggesting the presence of a central mechanism and that changes in sensitivity are directly correlated with clinical outcomes. 5 There is recent scientific evidence suggesting the presence of physical impairments in this population.…”
Section: T T Backgroundmentioning
confidence: 99%
“…The assessed locations have been reported to exhibit mechanical pain hypersensitivity as a sign of central sensitization in individuals with CTS. 12,17,18 The mean of 3 trials was calculated and used for the analysis. A 30-second rest was allowed between each measure.…”
Section: Neurophysiological Outcomesmentioning
confidence: 99%